Manusia di dalam Jaring Algoritma: Tinjauan Struktural dan Psikologi Karakter dalam Cerpen “Klik yang Membunuh” oleh Taufiqurohman - Putri Novitasari; Nori Anggraini (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study examines the short story "Click that Kills" by Taufiqurohman to reveal the position of humans in the increasingly dominating digital algorithm environment. Using a descriptive qualitative approach that focuses on structural analysis and literary psychology based on Freud's psychoanalytic theory, this study thoroughly analyzes the intrinsic elements as well as the inner conflicts of the characters. The findings of this study show that the AIDA system poses a profound existential crisis, where individual freedom is threatened due to systemic information manipulation. The characters of Dito and Genta experience a serious conflict between id, ego, and superego when dealing with the figure of "Shadow User" who is a real symbol of the shift in human dignity through raw data. In terms of structure, the storyline conveys a deep social critique of the loss of human self-control in cyberspace. This research shows that this short story is a premonious criticism of the importance of maintaining the essence of humanity in the midst of the prevalence of mechanical algorithms. The phenomenon emphasizes that digital technology can potentially alienate the moral consciousness of individuals in modern society.